Comparison Of Various Alogrithms In Different Loading Of Load Flow Analysis - Tajudin, Nur Atikah (Universiti Sains Malaysia, 2018)
Power flow analysis is the backbone of power system analysis and design. They are necessary for planning, operation, economic scheduling and exchange of power between utilities. The principal information of power flow analysis is to find the magnitude and phase angle of voltage at each bus and the real and reactive power flowing in each transmission lines. Power flow analysis is an important tool involving numerical analysis applied to a power system. In this analysis, iterative techniques are used due to the unavailability of analytical method to solve the problem. Many algorithms are being used to solve the problem of power flow in power system but the main algorithms always used are Newton Raphson method, Gauss Seidel method and Fast Decoupled method. The aim of this project is the comparison of various algorithms in different load loading of power flow analysis. Newton Raphson method, Gauss Seidel method and Fast Decoupled method in load flow analysis for different loading are implementation in this project using MATLAB R2017a. The set of nonlinear algebraic equations is solved using iteration methods. The results ware compared for number of iteration and the computational time taken. This research work are implemented using IEEE 14-Bus, IEEE 30-Bus and IEEE 57-Bus system.